ANALISA USAHA BUDIDAYA IKAN NILA MERAH (Oreochromis niloticus) SECARA TERPADU DENGAN AYAM (LONG-YAM) DI KABUPATEN BENGKULU UTARA - Ta'aladin, Zamdial (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
The objectives of this research were to know the feasibility of effort of Nila merah (Oreochromis niloticus) culture in integrated manner with chicken (Long-Yam). This research was conducted in Bengkulu Utara Regency, Bengkulu Province. The data were analyzed by financial-economic aspect using Net Benefit-Cost Ratio (Net B/C Ratio), NPV (Net Present Value) and IRR (Internal Rate of Return). The result of financialeconomic aspect analysis were obtained Net B/C Ratio = 1.71, NPV = 5,103,169 and IRR = 33,00. Based on the result of this analysis showed that the effort unit of nila merah (Oreochromis niloticus) culture in a integrated manner with chicken is feasible and can developed in Bengkulu Utara Regency.